Remote Worker's Survival Guide - Schindler, Esther (O'Reilly Media, Inc., 2016)
Telecommuting is an incredible way to work, especially for programmers and other tech workers. Besides the advantages of working from your own home (and avoiding rush hour), remote work offers independence, flexibility, and more control over your work environment. But it definitely has its challenges and tradeoffs. This report is packed with advice to help you make a success of telecommuting, whether you're an individual telecommuter, a team member, or a manager. Author Esther Schindler explains that successful telecommuting requires good communication skills, trust among colleagues, and shared dedication to accomplishing team goals. With this report, you'll learn to address two main challenges: how to organize your own life as a telecommuter, and how to work as part of a larger team. Manage your telecommuting life: create your own office space and give structure to your day Beat the workaholic syndrome so common with remote workers Define firm "on the job" times while making family a part of your daily routine Make yourself visible: stay in sync with colleagues through frequent and clear communication Find ways to collaborate with your team, including brainstorming sessions Deal with common technology problems you're likely to encounter.